2012
DOI: 10.1007/s00520-012-1554-0
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central catheters (PICCs) in the management of oncohematological patients submitted to autologous stem cell transplantation

Abstract: The aim of our study was to evaluate the feasibility and the safety of the use of peripherally inserted central catheters (PICCs) during autologous peripheral blood stem cell transplantation. Sixty PICCs were inserted in 57 patients (23 females and 34 males; mean age 48, range 19-68 years) and remained in place for an overall period of 1,276 days. All PICCs were positioned by a team of specifically trained physicians and nurses and utilized by specifically trained nurses of our hematology unit. No major insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 13 publications
9
53
1
1
Order By: Relevance
“…As previously mentioned, patients presenting with hematological malignancies were at higher risk of PICCrelated infections, and, particularly in patients necessitating an autologous or allogeneic stem cell transplantation (OR 6, 95 % CI [1.2-29.3]) whose PICC-related infection rate was 2.93 per 1000 catheter-days. This rate was pretty close to the one that Bellesi et al found in their cohort of 60 autologous peripheral stem cell transplantation procedures (2.3 per 1000 catheter-days) [18]. Worth et al also considered that the indication of hematopoietic stem cell transplantation as a potential PICC-related infection risk factor but did not obtained significant results [15].…”
Section: Microbiologymentioning
confidence: 64%
“…As previously mentioned, patients presenting with hematological malignancies were at higher risk of PICCrelated infections, and, particularly in patients necessitating an autologous or allogeneic stem cell transplantation (OR 6, 95 % CI [1.2-29.3]) whose PICC-related infection rate was 2.93 per 1000 catheter-days. This rate was pretty close to the one that Bellesi et al found in their cohort of 60 autologous peripheral stem cell transplantation procedures (2.3 per 1000 catheter-days) [18]. Worth et al also considered that the indication of hematopoietic stem cell transplantation as a potential PICC-related infection risk factor but did not obtained significant results [15].…”
Section: Microbiologymentioning
confidence: 64%
“…Few studies focusing on the use of PICCs in hematologic patients have been reported in the literature (Table 6) [4,6,[10][11][12]. These studies showed a variable and broad rate of CRBSIs, probably related to the technique of PICC insertion used (blind vs eco-guided), to the different criteria for the definition and detection of these complications, to the collection of data which was generally retrospective and to the [12].…”
Section: Discussionmentioning
confidence: 97%
“…In the last 10 years, after the introduction of ultrasonographic techniques to monitor PICCs' insertion, the rate of thrombosis has decreased significantly and has been reported to occur in about 2-5 % of patients [6,17,18]. A systematic review and meta-analysis of the literature aimed at comparing the frequency of venous thromboembolisms in PICCs and other CVADs has recently been published [18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent meta-analysis of 11 studies that compared the risk of thrombosis related to PICCs with that related to CVCs showed that PICCs were associated with an increased risk of catheter-related thrombosis (CRT) (odds ratio 2.55, 1.54-4.23, p<0.0001) [6]. Because of these concerns, only a few published studies have focused on the clinical usefulness and safety of PICCs in patients with HM, especially in those receiving intensive chemotherapy [2,3,[7][8][9][10][11][12]. A comparison between these published studies and our current study needs to be carefully performed because the population, endpoints, and definitions greatly varied in these previous studies.…”
Section: Introductionmentioning
confidence: 97%